Capital Structures on Financial Performance of Medium Sized Enterprizes in Mukono Town:A Case Study of Paris Corner Supermarket Mukono Uganda - Janet Tumusiime Atukunda (Uganda Christian University, 2024)
The capital structure is one of the most vital topics in finance, majorly about the optimal capital structure that will bring greater financial value to medium-sized enterprises. This study tried to ascertain the effect of the capital structure on a firm's performance in the case of the Paris Corner supermarket. The research was based on the objectives meant to establish the following: the relationship between capital structure and financial performance of medium-sized enterprises in Mukono, the effect of debt financing on the financial performance of medium-sized enterprises in Mukono, and finally, the effect of equity on financial performance of medium enterprises in Mukono. Chapter 1 represents the background of the study for this research; it also states the problem of the study which was identified as the declinig profitability and liquidity of medium sized enterprises as a result of poor financial decisions when it came to selecting an appropriate capital structure to employ in their business, its objectives, and the purpose. It then presents the research questions, scope of the study, and its significance. Chapter 2 goes ahead to represent the literature-reviewed. Literature on capital structures on financial performance of medium-sized enterprises and the understanding of different scholars on such variables. Chapter 3 represents the research methodology, consisting of a description of the research design, study population sample size, data collection instruments used and in this case questionnaires were administered, data quality, that is reliability and validity, and methods of data presentation. Chapter 4 then gives the findings of the research in reference to the research objectives. Presentation of the data was done through tabulation for easy understanding. Finally, which is the last chapter, chapter 5 summarizes data in a more exact way. It also gives the recommendations and conclusions of the study.